Evaluation théorique de la protection de l’acier doux contre l’effet d’un milieu corrosif par des composés organiques contenant des hétéroatomes - Kahla, Nabil; Hammadi, Lamia; Abd Elhak, Belmehdi; Djafour, Achouak; Guerfi, Nadir (université d'eloued, 2023)
"Density Functional Theory (DFT) was used to calculate the globalreactivity parameters and Millikan charges descriptors as well as SAR parameters show some positive agreement with the experimental results of the responsible for the electron transfer from the studied inhibitor molecules to the mild steel to stop the as well as structure activity relationship SAR analysis to bridge the gap between the effect of electronic b][1,2,4,5]tetrazine (HTA)and azelaic acid dihydrazide (AZA). The obtained results of the global reactivity using two molecules namely 6-(4-hydroxyphenyl)-3-mercapto-7,8-dihydro-[1,2,4]triazolo[4,3- corrosion inhibition efficacies. The analysis of Millikans charges gives a comprehensive view of the atoms properties at the molecular level and the corrosion inhibition efficiency of mild steel in an acidic medium corrosion mechanisms." تم استعمال نظرية الكثافة الوظيفية DFT لحساب موصفات التفاعلية الكلية و مؤشرات التفاعلية المحلية المعروفة بوظائف فيكوي Fukui functions بالإضافة إلى حساب معاملات علاقة البنية الهيكلية بالفعالية SAR لفهم تأثير الخصائص الإلكترونية على المستوى الجزيئي على مردود تثبيط تآكل الفولاذ الطري في وسط حمضي باستعمال جزيئتي 6- (4-هيدروكسي فينيل) -3-مركابتو -7،8-ثنائي هيدرو- [1،2،4] تريازولو [4،3-ب] [1،2،4،5] تترازين و ثنائي هيدرازيد حمض الأزيليك كلا على حدا. تُظهر نتائج مؤشرات التفاعلية الكلية التي تم الحصول عليها و كذا مؤشرات SAR توافقا ايجابيا مع النتائج التجريبية لمردود تثبيط التآكل. يعطي تحليل مؤشرات التفاعلية المحلية عرضا شاملا للذرات المسؤولة عن النقل الإلكتروني من الجزيئتين المدروستين الى الفولاذ الطري لكبح ميكانيزمات التآكل.
مذكرة ماستر هندسة كيميائيةDes thèses génie chimique
Keywords: "Density Functional Theory, global reactivity parameters, Millikan charges, structure activity relationship, corrosion inhibition, 6(4hydroxyphenyl)3mercapto7,8dihydro[1,2,4]triazolo[4,3 b][1,2,4,5]tetrazine, azelaic acid dihydrazide."; نظرية الكثافة الوظيفية، موصفات التفاعلية الكلية، مؤشرات التفاعلية المحلية، معاملات علاقة البنية الهيكلية بالفعالية، تثبيط تآكل، 6- (4-هيدروكسي فينيل) -3-مركابتو -7،8-ثنائي هيدرو- [1،2،4] تريازولو [4،3-ب] [1،2،4،5] تترازين، ثنائي هيدرازيد حمض الأزيليك.